Sindromul Nina Zarecinaia - Purea, Elena (Theatrical Research, 2023)
Nina Zarechnaya Syndrome Nina Zarechnaya is metaphorically seen in this research paper as a prototype of the apprentice in acting, as she is clearly a teenager facing the decision to engage in an artistic career and the ensuing hold-backs, such as her desperate attempts to perform, which culminate in personal and professional failure. In my paper, I have attributed a type of syndrome to this famous character, as a label for a great number of obstacles acting students have to overcome.